Margin Pemasaran Ikan Pari Mondol (Himantura gerrardi) di Kelurahan Kawal Kabupaten Bintan: Marketing Margin of Stingray Mondol (Himantura gerrardi) in Kawal Village, Bintan Regency - Nasution, Lisa Uswatun Hasanah; Khairunnisa, Khairunnisa; Tetty, Tetty (MarIslands, 2024)
The research aims to determine 1) the marketing channels of Mondol stingrays; and 2) marketing margins for Mondol stingrays. The research method used is a combination research method. The results showed that there were four marketing channels in Kawal Village: 1) Fishermen- Consumers; 2) Fishermen - Middlemen Consumers; 3) Fishermen - Middlemen - Merchants Collectors - Consumers; 4) Fishermen - Middlemen- Retailers-Consumers. Marketing margins on marketing channels are different in each marketing channel.